Understanding the Performance Effects of "Dark" Salesperson Traits: Machiavellianism, Narcissism, and Psychopathy. (March 2023) - Satornino, Cinthia B.; Allen, Alexis; Shi, Huanhuan; Bolander, Willy
People with the personality traits of Machiavellianism, narcissism, and psychopathy (i.e., the "dark triad") are prevalent in the sales profession. Yet research into sales performance drivers tends to focus on positive personality traits. The authors examine the dark triad's effect on salesperson performance and reveal some conditioning factors that influence these links. A longitudinal study that pairs surveys and objective performance data from a national insurance agency reveals the complex effects of dark triad traits on performance over time. Another study, based on data from a direct sales organization and employing social network analysis, relies on partial least squares structural equation modeling to determine the role that the social structure plays in conditioning the relationship between dark triad traits and performance. The results yield insights into both the challenges and the opportunities that dark traits present for managers and scholars.